أثر الترويج على سلوك المستهلك (دراسة تطبيقية على شركة دال للمواد الغذائية 2015 - 2020م) - أ.د. البشير التيجانى محمد الشايب,; د. عبدالله إبراهيم أبكر عبد الله, (White Nile Journal for Studies and Research, 2022)
The study dealt with the impact of promotion on consumer behavior in Dal Foodstuff Company Sega Flour Mills. The problem of the study was that there was a weakness in the promotion process that affected the consumer behavior of Dal Foodstuff Group. The importance of the study was to confirm the importance of promotion and its role in maintaining customers through Increasing behavioral awareness. The study aimed to identify the shortcomings with regard to the process of promoting Dal Foodstuff Company, as well as to show the impact between promotion and consumer behavior of the company and customers. Size is 150 singles Distributed to employees at Siga Flour Mills, and the study reached several results, the most important of which is that cultural programs have an impact on the consumer's mentality, and that the direct selling unit seeks to achieve full consumer satisfaction, To motivate them to be able to convince customers of products with ease